2017
DOI: 10.1002/jor.23543
|View full text |Cite
|
Sign up to set email alerts
|

Bone robusticity in two distinct skeletal dysplasias diverges from established patterns

Abstract: Identifies morphologic trends in two distinct skeletal dysplasia populations (OI and ACH) to better understand development of bone robusticity and slenderness in humans. Understanding these patterns of bone morphology is important to predict how individuals will respond to treatment and to increase treatment effect. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2392-2396, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“… Note : Green values are positive significant correlations and red values are negative significant correlations ( P < .05). Hand radiograph parameters legend : 30%, 40%, 50%, 60% = length measurements of the metacarpal (eg, 30% = 30% of the length of the second metacarpal in millimeters). Marrow diameter at 50% = diameter of the marrow (distance between inner cortices) at 50% length of the metacarpal.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“… Note : Green values are positive significant correlations and red values are negative significant correlations ( P < .05). Hand radiograph parameters legend : 30%, 40%, 50%, 60% = length measurements of the metacarpal (eg, 30% = 30% of the length of the second metacarpal in millimeters). Marrow diameter at 50% = diameter of the marrow (distance between inner cortices) at 50% length of the metacarpal.…”
Section: Methodssupporting
confidence: 80%
“…The BHI measurement incorporates cortical area, length and width of the metacarpal. In addition, these and other morphological parameters (see Table ) were assessed separately, as they may also be associated with bone quality and strength . A portable NIR spectrometer (ASD LabSpec 4) equipped with a 3 mm diameter fiber optic probe comprise of six low OH fibers for illumination and one for collection was used to transcutaneously obtain NIR spectra from the middle, dorsal region of the M2 bone of OI patients (Figure 1C).…”
Section: Methodsmentioning
confidence: 99%
“…A study on 24 adults with OI found that the length of the second metacarpal was normal in 22 of these individuals, but no information about OI types was provided (12). In an analysis of 39 children and adults with OI, the length of the second metacarpal was lower than in age-and sex-matched controls, but results were not broken down by OI type (14). We had previously studied the length of the second metacarpal in a group of 42 children with OI type I and found a mean z-score of +0.1 (13).…”
Section: Discussionmentioning
confidence: 97%
“…A few studies have measured the length of the second metacarpal in individuals with OI and reported normal results for most study participants (12)(13)(14). However, these studies were small (42 participants or less), did not report genotype information and either exclusively focused on OI type I (13) or did not compare results between different OI types (12,14). It remains therefore unknown whether metacarpal length differs between OI types or is related to genotype.…”
Section: Introductionmentioning
confidence: 99%
“…In various human long bones, Ct.Ar has been shown to positively correlate with robustness (e.g., Tt.Ar/Bone Length), whereas Rt.Ct.Ar demonstrates the inverse relationship (Citron et al, ; Jepsen, Bigelow, & Schlecht, ; Schlecht, Bigelow, & Jepsen, ; Schlecht & Jepsen, ). Similarly, robust bones (i.e., wide relative to length) tend to be less mineralized than slender bones (i.e., narrow relative to length) (Tommasini, Nasser, Hu, & Jepsen, ; Jepsen et al, , ; Schlecht & Jepsen, ; Goldman et al, ; Schlecht et al, 2014).…”
Section: Discussionmentioning
confidence: 99%